2022
DOI: 10.1111/tpj.15765
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on silica biomineralization by comparative analysis of the silica‐associated proteomes from three diatom species

Abstract: SUMMARY Morphogenesis of the intricate patterns of diatom silica cell walls is a protein‐guided process, yet to date only very few such silica biomineralization proteins have been identified. Therefore, it is currently unknown whether all diatoms share conserved proteins of a basal silica forming machinery, and whether unique proteins are responsible for the morphogenesis of species‐specific silica patterns. To answer these questions, we extracted proteins from the silica of three diatom species (Thalassiosira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
2
13
0
4
Order By: Relevance
“…Frustule mineralization is an obligatory part of the lifecycle of many (but not all) of the thousands of extant diatom species [7]. A cadre of biomolecules have now been identified that seem to be dedicated to frustule formation [4,[8][9][10][11][12][13][14][15][16][17], and understanding the molecular basis of silicification remains an active area of study [18].…”
Section: Introductionmentioning
confidence: 99%
“…Frustule mineralization is an obligatory part of the lifecycle of many (but not all) of the thousands of extant diatom species [7]. A cadre of biomolecules have now been identified that seem to be dedicated to frustule formation [4,[8][9][10][11][12][13][14][15][16][17], and understanding the molecular basis of silicification remains an active area of study [18].…”
Section: Introductionmentioning
confidence: 99%
“…2I, K, M, Supplementary Fig. 9B, D, 10G, 12G) 22 , and in dank2KO mutants the distal tubes are missing in all fultoportulae (Fig. 2L, Supplementary Fig.…”
Section: Functional Analysis Of Dank Proteins In Vivomentioning
confidence: 95%
“…In the past, the discovery of proteins involved in silica morphogenesis was severely hampered by the lack of a method for isolating SDVs. Therefore, biochemical analyses of diatom cell walls [19][20][21][22] and transcriptomics analyses of synchronized diatom cell cultures has been pursued 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Once valve morphogenesis inside the SDV is complete, the new silica valve is exocytosed and integrated into the cell wall [12], [13]. In recent years, tremendous progress has been made in diatom research regarding sequencing and targeted manipulation of genomes [16], as well as the identification of candidate silica biogenesis proteins [17]- [19]. However, the physical principles that govern morphogenesis of the hierarchical silica patterns in diatoms are still enigmatic.…”
Section: Introductionmentioning
confidence: 99%